Linkages, Potential, and Spatial Efficiency of Paddy Production in East Java - Nugroho, Ris Yuwono Yudo (Journal of Developing Economies, 2016)
East Java has a big role in supplying agricultural product for nasional logistic. The problems are not completely resolved, regional development planning should integrate sectoral and spatial approach. The focus of study is to analyze the linkage of rice production to other sectors, in order to develop rice production. Research using the Input-Output models, Location Quotient to measure the degree of relative specialization of a region, and DEA to measure the performance of spatial efficiency. The result used IO table in 2010, contributors backward linkage of paddy sector are paddy sector itself, fertilizer and pesticide sector, also agriculture services and hunting, while the backward linkage contributors are paddy sector itself, rice sector, and food products and beverages. Spatially there are 28 areas that are able to serve the market of paddy products. If related to production efficiency, there are nine areas are included in the category of efficient production, with input in the form of land, and the number of farmers. Policy Implication related to the findings of input output approach, are the affordability of input proces, the streamlined of input distributing system, and the goes on education and information to the farmer about input usage. Whereas, related to the spatial aspect, in soft infrastructure as strengthening internal capacity of farmer and instructor. In the other hand, hard structure aspect especially restoration of irrigation, allocating best seed and fertilizer for farmer.